Measurement of engagement of student-centered learning practices in Malaysian higher learning institutions - ., Vighnarajah (2014)
Criticisms escalated among relevant stakeholders in the Malaysian job market and Malaysian educational system as allegations were made towards Malaysian Higher Leaming Institutions for not encouraging rehearsal of soft skills among graduates. This stirred deep concems for the lack of student-centered leaming practices in promoting development and rehearsal of soft skills. Through the implementation of the National Higher Education Strategic Plan (pelan Strategik Pengajian Tinggi Negara, PSPTN), the fonner Ministry of Higher Education alIDounced that focus will be channeled towards student-centered leaming practices to cultivate development and rehearsal of student-centered leaming practices. On these convictions, a growing number of Malaysian Higher Leaming Institutions have begun to channel interest in adopting student-centered leaming practice, though it has surfaced to attention that many instructors and students have a general misconception on proper student-centered learning practices. With the theoretical understanding of the student-centered learning being at odds with its pedagogical practice, it is alarming to discover that most instruments currently available only measures distinct elements of student-centered leaming practices. As it becomes increasingly uncertain to what extent instructors and students are engaged in studentcentered learning practices, this study attempts to develop a statistically valid and reliable instrument to measure student-centered leaming practices in Malaysian Higher Leaming Institutions. This study adopted a mixed methods research design, commencing with the qualitative phase and completing on a quantitative phase. The study commenced with the qualitative phase which involved in-depth interviews with four professors prominent in their field for advocating student-centered learning practice. The quantitative phase involved development of the items, content validity testing via Delphi technique, face validity and reliability testing through the Validation of Items stage, and construct validity testing via exploratory factor analysis. The sample size for the factor analysis was 1091 students, randomly selected from the four research universities; namely, Universiti Malaya (UM), Universiti Kebangsaan Malaysia (UKM), Universiti Putra Malaysia (UPM), and Universiti Sains Malaysia (USM). Analysis of the in-depth interview findings led to the emergence of five constructs that describe student-centered learning practices in Malaysian Higher Learning Institutions. These five constructs were meaningful learning, effective assessment,development of soft skills, contextual resources and instructors as facilitators . For each construct, approximately 15-23 items were developed leading to a total of 101 items for the entire instrument. The development of these items was substantiated with excerpt evidences from the in-depth interviews, as well as literature governing student-centered leam.i.ng practice. Based on the Delphi analysis, there were 52 items that were recognized to essentially reflect characteristics of student-centered learning practices in Malaysian Higher Learning Institutions. For the exploratory factor analysis, principal component analysis (PCA) with varimax rotation was used to determine the number of components to retain and categorization of items in their respective components. Based on these findings, six components and 46 items were retained with a total cumulative variance of 59.921 %; Rehearsal of Soft Skills, Rehearsal of Meaningful Leaming, Rehearsal of Instructor Facilitation, Rehearsal of Effective Assessment,Rehearsal of Self-Regulation, and Rehearsal oflnfonnation Searching Skills.